Determinants of Financial Derivative Disclosures in an Emerging Economy: A Stewardship Theory Perspective - Hima Bindu Kota; B. Charumathi (Australasian Accounting, Business and Finance Journal, 2018)
The accounting system in India is undergoing a significant change. With the notification of Companies (Indian Accounting Standards) Rules 2015, the Ministry of Corporate Affairs in India converged the Indian Accounting Standards (Ind AS) with International Financial Reporting Standards (IFRS) which was applied in a phased manner from 1 April 2016 beginning with large companies whose net worth was equal to or exceeded INR 5 billion, followed by its implementation for smaller companies with net worth between 2.5 billion to 5 billion thereafter. Among other accounting standards, Financial Instruments Standards Ind AS 32, 109 and 107 that defines, recognises, measures and specifies disclosure norms of financial instruments including financial derivatives were introduced. Warren Buffet very famously called derivatives, “financial weapons of mass destruction,” and giving credence to his views, time and again, financial as well as non-financial firms in India and around the world have sustained losses due to the usage of financial derivatives. Over the years, the capital markets have changed, and business models have become more challenging with complex sources of risk and uncertainty which has transformed risk management into a sophisticated art. This complex and ever-changing business environment has brought to the fore the necessity and importance of developing reliable and relevant disclosure norms to help protect all stakeholders, as derivatives, due to their underlying complex nature, can be a significant source of systematic risk. This is also reiterated, with shareholders and investors stepping up the demand for increased financial disclosure. This empirical study models the factors that determine Financial Derivative Disclosure of Indian non-financial firms The study develops a self-constructed unweighted Financial Derivative Disclosure Index (FDDI) to measure the derivative disclosure. The sample represents companies from Nifty 50, out of which banking and financial services companies were removed. Using multiple regression model, this study modelled the corporate governance factors which determine derivative disclosure. The factors identified were presence of usage of derivatives, size, foreign income, presence of risk management committee, institutional shareholding and binary variable for family business. The results show that the stewardship theory explains the determinants of financial derivative disclosure in Indian context, and promoters act as stewards and guide their firms to improve their financial derivative disclosures.
Keywords: Accounting Standards 32; 109 & 107; Financial Derivative Disclosure Index (FDDI); Financial Derivative Disclosure Quotient (FDDQ); derivative usage; Nifty 50.